Population, Migrations and Development - (:unkn) unknown (My University, 1994)
Rapid demographic growth in Africa has not been accompanied by economic development. It has generated important flows to the North. Family planning programs will not be sufficient to solve the problems caused by the demographic growth and they will most likely increase in the future. Controls of these flows are unikely to be effective. Under these conditions, only the economic development of the South will allow the limitation of outmigration.
Keywords: African Research